DEIXIS IN PEKAL LANGUAGE OF NORTH BENGKULU REGENCY - Syamsurizal . (Metalingua: Jurnal Penelitian Bahasa, 2015)
THE 21st century is predicted to bring changes to the world's economy and culturewhich is hence feared to affect local languages and culture, including that ofPekal language. To avoid it from happening, a research on Pekal language iscarried out in this article. It aims at describing the Pekal language's deicticpersona, time, place, and discourse used by its speakers in the Districts of Ketahunand Napalputih, the North Bengkulu Regency. It used descriptive qualitativemethod. The data were collected using listening and speaking method withstimulating, writing, and recording techniques. The result showed that the deicticform of the first person singular is akui while those of the plural are aok, kami/kaming, and kitung 'we'; the deictic forms of second person singular are ikau,aban/kaban, and mamang, while those of the second person plural are kamisiko and masiko 'you all'; the third person singular deictic are iyu/iyung 'he/she',-yung and ikau, while the third person plural deictic are masiko, asiko, andtoboh de. Deictic of time were petang 'yesterday', kining 'now', tading 'just now',paging 'tomorrow', siang, metang 'afternoon', senju 'evening', malam, biae 'havebeen to', awit/garang 'often', terus 'always', kadang kaleu 'sometimes', biasoyung'usually', kining 'at present', kalu 'if', dan bilu 'when'. the deictic of discourse arewords/phrases such as iko, itu/tunah, cak iko/cak konah, nyo, yung, cak itu.Among the deictic of person, only the third person that could be marked asanaphoric or cataphoric. The anaphoric deictic was divided into two entities,namely singular (-yung, e) and plural (-masiko 'you', toboh tui 'they')